2018
DOI: 10.1002/lno.11002
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nitrogen loading controls summer cyanobacterial blooms without promoting nitrogen‐fixing taxa: Long‐term response of a shallow lake

Abstract: The effectiveness of controlling nitrogen (N) to manage lake eutrophication is debated. Long-term, wholelake case studies are required to determine whether diazotrophic cyanobacteria can fix sufficient N to offset a reduction of N-inputs. We document the recovery of shallow, productive Lake Müggelsee (Germany) over 37 yr (sampling interval 1-2 weeks) during a decrease of N and phosphorus (P) loading of 79% and 69%, respectively. Nitrogen concentrations in the lake responded immediately to loading reduction whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 51 publications
2
61
0
Order By: Relevance
“…In their review of 89 control efforts McCrackin et al () did not find any significant differences in success from efforts to control P, N, or N + P, but variability was high, and few management programs have attempted to control N alone. Nevertheless, dual N and P control is beginning to be implemented with some success, either in experimental situations, or in entire systems (Baker et al, ; Elmgren & Larsson, ; McCrackin et al, ; Shatwell & Köhler, ). Agencies in the U.S. and Europe are drafting regulations to enforce dual nutrient control (EPA, ; Ferreira et al, ).…”
Section: Managing Nutrients In Complex and Linked Stream‐lake‐marine mentioning
confidence: 99%
“…In their review of 89 control efforts McCrackin et al () did not find any significant differences in success from efforts to control P, N, or N + P, but variability was high, and few management programs have attempted to control N alone. Nevertheless, dual N and P control is beginning to be implemented with some success, either in experimental situations, or in entire systems (Baker et al, ; Elmgren & Larsson, ; McCrackin et al, ; Shatwell & Köhler, ). Agencies in the U.S. and Europe are drafting regulations to enforce dual nutrient control (EPA, ; Ferreira et al, ).…”
Section: Managing Nutrients In Complex and Linked Stream‐lake‐marine mentioning
confidence: 99%
“…One reason for focussing on P rather than N is the belief that N fixation by certain cyanobacteria may allow an escape from N limitation (Schindler 1977). However, evidence is growing that N fixation is inadequate to overcome N limitation (Shatwell andKohler 2019, van Gerven et al 2019). A Policy Forum Review in Science concluded that amelioration of the negative impacts of nutrient enrichment should be made by control and reduction of both N and P (Conley et al 2009); more recent work supports this contention (Lewis et al 2011, Wurtsbaugh et al 2019.…”
Section: Implications Of Nutrient Limitation Status and Managementmentioning
confidence: 99%
“…After very high nutrient loadings into Lake Müggelsee during the 20th century peaking in the 1970s and 1980s, nutrient loads started dropping steeply in the beginning of the 1990s and continued reducing after year 2000 [21]. In parallel with the high nutrient loading, almost all macrophytes disappeared from Lake Müggelsee in the 1970s.…”
Section: Studied Lake System and Impact Of Bank Filtrationmentioning
confidence: 99%